The Educational Values of the Dewi Sekartaji Figure in Wayang Timplong of Asmarabangun Murco Story - Riski Utma Dona; Mulyanto Mulyanto; Margana Margana (Yayasan Keluarga Guru Mandiri, 2023)
This study aims to determine the value of character education in the Dewi Sekartaji figure in Wayang Timplong. This study was designed qualitatively, with data collected through interviews, observation, and document analysis. The study was carried out in Nganjuk Regency. The puppeteers (dhalang) and Wayang Timplong craftsmen were the study informants. The results show that 1) The Wayang figure of Dewi Sekartaji composes of gabahan eyes, ambangir nose, damis mouth, torso putri sariro, bolo arms, bokongan satrio, suku bambang legs, dodot putren clothing, putren bracelet jewelry, white and bromine. 2) The value of character education embedded in the dialogue and visual form of Wayang includes assertive, responsible, religious, independent, smooth, sharp, tough, skillful, warrior, innocent, alusan ‘gentle’, modest princess, gentleness, holy, faithful, nobility, wise, vigilant, determination, struggle, devotion, noble, and noble characters. This study finds that the Dewi Sekartaji figure is relevant with five-character education values, including religious (gentle, patient, innocent, smiling, holy, believing, religious, firm), nationalism (perwira ‘commander’, warrior, devoted), independent (sharp, tough, skillful, agile, vigilant, fighter, independent), integrity (good, wise, honest, simple, loyal, great, responsible, assertive). This research can be used as inspiration for learning materials and can be used as reference and comparison material for researchers who will conduct research with the same focus.